Back and neck pain: A comparison between acute and chronic pain-related Temporomandibular Disorders - Jack Botros; Mervyn Gornitsky; Firoozeh Samim; Zovinar der Khatchadourian; Ana Miriam Velly (Taylor & Francis Group, 2022)
Background Temporomandibular disorders (TMDs) are common and cause persistent pain. Comorbidities are associated with TMDs and can affect the effectiveness of their treatments. The literature is lacking enough evidence on the difference between acute and chronic pain, particularly in TMDs. Investigating this difference could highlight potential risk factors for the transition from acute to chronic pain-related TMDs.Aim To compare the likelihood of back and neck pain (BP, NP) between acute and chronic pain-related TMDs (AP-TMD, CP-TMD) as defined by pain duration and pain-related disability.‎Methods Participants with AP-TMDs (≤3 months) and CP-TMDs (>3 months) were recruited according to the diagnostic criteria and research diagnostic criteria of TMD. BP and NP were assessed using a self-reported checklist. CP-TMDs defined by disability (chronic disability) and depression and anxiety symptoms were assessed using validated instruments. Logistic regression analyses were employed.Results This study enrolled 487 adults with AP-TMD (n = 118) and CP-TMD (n = 369). Relative to AP-TMD, participants with CP-TMD had twice the odds of reporting NP (odds ratio [OR] = 2.17‎, 95% CI 1.27-3.71) but not BP ‎‎(OR = 0.96, 95% CI 0.57-1.64). Participants with chronic disability were twice as likely to report NP ‎(OR = 1.95‎, 95% CI 1.20-3.17‎) but not BP (OR = 1.13, 95% CI 0.69-1.82)‎ compared to those without. All analyses were adjusted for age, sex, and anxiety and depression symptoms.Conclusions Within the limitations of this study, results suggest that central dysregulation or trigeminocervical convergence mechanisms are implicated in the process of pain-related TMD chronification and highlight the relevance of considering disability when defining CP-TMDs.